Dual activities of a silencing information regulator complex in yeast transcriptional regulation and DNA‐damage response - Josephine Rybchuk; Wei Xiao (mLife, 2024)
Abstract The Saccharomyces cerevisiae silencing information regulator (SIR) complex contains up to four proteins, namely Sir1, Sir2, Sir3, and Sir4. While Sir2 encodes a NAD‐dependent histone deacetylase, other SIR proteins mainly function as structural and scaffold components through physical interaction with various proteins. The SIR complex displays different conformation and composition, including Sir2 homotrimer, Sir1‐4 heterotetramer, Sir2‐4 heterotrimer, and their derivatives, which recycle and relocate to different chromosomal regions. Major activities of the SIR complex are transcriptional silencing through chromosomal remodeling and modulation of DNA double‐strand‐break repair pathways. These activities allow the SIR complex to be involved in mating‐type maintenance and switching, telomere and subtelomere gene silencing, promotion of nonhomologous end joining, and inhibition of homologous recombination, as well as control of cell aging. This review explores the potential link between epigenetic regulation and DNA damage response conferred by the SIR complex under various conditions aiming at understanding its roles in balancing cell survival and genomic stability in response to internal and environmental stresses. As core activities of the SIR complex are highly conserved in eukaryotes from yeast to humans, knowledge obtained in the yeast may apply to mammalian Sirtuin homologs and related diseases.